The role of Kazan printing houses in printing books in the Kazakh language at the beginning of the 20th century - Kuantayev Н.Қ; Khibadullina А.С.; Kairatov Ж.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
This article examines the emergence of Kazakh printed books published in Kazan printing houses in the early 20th century, as well as the potential and challenges of their use. The article’s primary objective is to analyze Kazan’s contribution to the development of Kazakh spirituality and book printing in the late 19th and early 20th centuries, including the publication of the first books in the Kazakh language, as well as the role of printing houses in the educational field of that period. It also identifies the development of book printing, the content, thematic features, and historical significance of printed materials, and defines their place in Kazakh national culture and education. The research methodology utilizes analysis, data processing, and expert evaluation. The study’s significance lies in the analysis of archival documents, periodicals, and scholarly works related to printed books and printing houses in the Kazakh language published in Kazan in the early 20th century. The results of the study demonstrate that the activities of various printing houses, the content of printed materials, and their distribution were determined using a method of source systematization and comparative analysis. The article emphasizes the influence of book printing in Kazan on the formation of Kazakh spirituality.